Electric field effects on the electronic and optical properties in C2N/Sb van der Waals heterostructure. (April 2018) - Wang, Xiaolong; Quhe, Ruge; Cui, Wei; Zhi, Yusong; Huang, Yuanqi; An, Yuehua; Dai, Xianqi; Tang, Yanan; Chen, Weiguang; Wu, Zhenping; Tang, Weihua
Abstract: Development of novel van der Waals (vdW) heterostructure is of great interest and significant to improve the performance of photovoltaic, photocatalytic and optoelectronic devices. In this work, the C2 N/ β -Sb vdW heterostructure has been investigated by the first-principles calculations. It is found that the pristine C2 N/ β -Sb vdW heterostructure is a type-ΙΙ heterostructure with a direct band gap of 1.2eV, and has a number of desired optoelectronic properties that are suitable for use in a solar cell. The external electric field can effectively modulate band alignment and affect the optical properties of the C2 N/ β -Sb heterostructure. The energy conversion efficiency of the pristine heterostructure is 22.86%, and the energy conversion efficiency can be increased under the negative electric field. Our results show that the C2 N/ β -Sb vdW heterostructure possesses great potential to be high-performance optoelectronic device. Graphical abstract: Image